A feasibility study for CO2 geological storage in Northern Italy. (December 2016) - Colucci, F.; Guandalini, R.; Macini, P.; Mesini, E.; Moia, F.; Savoca, D.
Highlights: Lombardia is the Italian Region with the largest release of CO2 in the atmosphere. The study assess the possibility to design a CCS pilot plant in a saline aquifer. Caprock-reservoir system has been identified in clay and conglomerate formations. 3D geological and numerical model of CO2 geological storage are presented. The investigated system seems compatible with potential CCS pilot plant. Abstract: The research concerns the assessment of the possibility to design a CCS pilot project in a deep saline aquifer of Northern Italy (Lombardia Region), one of the most populated and industrialized area of the Country. Lombardia Region emits about 70 Mt CO2 per year, ranking the Region as the largest Italian producer. The study area covers an area of about 1500 km 2, and the potential caprock-reservoir system has been identified in a clay and conglomerate formation, respectively. A 3D static geological model and a 3D fluid-dynamic model have been implemented in order to analyze the CO2 storage process. After the evaluation of the storage capacity of the geological system identified in the study area, six different injection scenarios have been simulated, by considering 30 years of fluid injection at a rate of 0.3 Mt of CO2 per year. For a preliminary assessment of safety conditions, CO2 plume size, volume and displacement, together with overpressures distribution at the caprock-reservoir boundary have been simulated and analyzed. This study represent a first step for the evaluation of the storage capacity of the study area, and the results of the numerical simulations seems to confirm the possibility to develop a CCS pilot project in the future. The numerical simulations confirm, amongst the other, that the geological system is compatible with the storage of a mass of CO2 consistent with the design of a pilot project. However, further analyses are necessary (such as detailed site-investigations to confirm some geological assumptions and exhaustive geomechanical studies) before considering this area fully suitable for CCS.